2017
DOI: 10.1039/c7cc02162c
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside-linked shunt products in the reaction catalyzed by the class C radical S-adenosylmethionine methyltransferase NosN

Abstract: NosN is a class C radical S-adenosylmethionine (SAM) methyltransferase (RSMT) involved in the biosynthesis of nosiheptide, a clinically interesting thiopeptide antibiotic produced by Streptomyces actuosus. NosN employs an unprecedented catalytic mechanism, in which SAM is converted to 5'-methylthioadenosine (MTA) as a direct methyl donor. In this study, we report identification of several nucleoside-linked shunt products in the NosN-catalyzed reaction. Comparative analysis of NosN and the class A RSMT RlmN and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…S -guanosylmethionine and S -cytidinylmethionine) have provided indirect support for this mechanistic proposal. 32 The work on NosN presents a new paradigm for cobalamin-independent rSAM MTs. Whether this proposed mechanism holds for other class C rSAM MTs remains an area of active investigation.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…S -guanosylmethionine and S -cytidinylmethionine) have provided indirect support for this mechanistic proposal. 32 The work on NosN presents a new paradigm for cobalamin-independent rSAM MTs. Whether this proposed mechanism holds for other class C rSAM MTs remains an area of active investigation.…”
Section: Ripp Biosynthetic Reactions Catalyzed By Rsam Enzymesmentioning
confidence: 99%
“…The methyltransferase activity of the class C radical SAM enzyme NosN has been recently reconstituted in vitro in our lab, which was shown to install a methyl group on the indole C4 of the MIA moiety 32 , 33 . Neither MIA ( 3 ) nor 2 is the NosN substrate, while this enzyme was shown to methylate 9 , an N -acetylcysteamine (SNAC) thioester derivative of MIA, to produce 10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that the radical SAM methyltransferase NosN is responsible for attaching a methyl group on the C4 of MIA moiety and this methylation reaction involves a key methylene radical derived from 5′-methylthioadenosine, a SAM cleavage product 32 , 33 . The nosN -knockout mutant of S. actuosus produced a nosiheptide analogue ( 2 ), which contains an indolyl- S -cysteine moiety, whereas the side ring is not formed 14 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes, which are characterized by sequence homologies with HemN (Layer et al, 2002 ) are referred as class C radical SAM methyl-transferases in contrast to B 12 -dependent radical SAM enzymes which belong to class B methyl-transferases (Zhang et al, 2011b ). Two enzymes, TbtI and NosN, involved in, respectively, the biosynthesis of the thiopeptide thiomuracin (Mahanta et al, 2017 ) and nosiheptide (Ding et al, 2017a , b ), have been recently characterized. In an unexpected manner, it has been proposed that NosN uses the SAM cofactor to generate not only 5′-dA but also 5′-methylthioadenosine (MTA) (Ding et al, 2017a ).…”
Section: Radical Sam Enzymes Involved In Ripp Methyl Transfer Reactiomentioning
confidence: 99%